Atlantic Bonds : A Nineteenth-Century Odyssey from America to Africa - Lindsay, Lisa A. (Book collections on Project MUSE., 2017)
"A decade before the American Civil War, James Churchwill Vaughan (1828-93) set out to fulfill his formerly enslaved father's dying wish: that he should leave his home in South Carolina for a new life in Africa. He traveled first to Liberia, then with Southern Baptist missionaries to "Yoruba country." Over the next forty years in today's southwestern Nigeria, Vaughan was taken captive, served as a military sharpshooter, built and re-built a livelihood, led a revolt against white racism, and founded a family of activists"--